2021
DOI: 10.1186/s13018-021-02766-y
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcomes of revision total knee arthroplasty in patients with septic loosening compared to patients with aseptic loosening

Abstract: Background The purpose of this study was to compare the functional outcomes, activity levels, mortalities, implant survival rates, and complications in revision total knee arthroplasty (TKA) of patients with septic loosening with those in patients with aseptic loosening over a minimum 10-year follow-up period. Methods A cohort of 78 patients (36 septic loosening and 42 aseptic loosening) was selected between January 2008 and December 2009. The fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The mean MINORS score was 20.5 (range, 18 to 22). Unblinded evaluation of objective and subjective end points was the main limitation that detracted from 14,18 .…”
Section: Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The mean MINORS score was 20.5 (range, 18 to 22). Unblinded evaluation of objective and subjective end points was the main limitation that detracted from 14,18 .…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Complications (Reoperation, Infection, and Failure Rates) Seven studies 9,12,14,[19][20][21][22] and 1,190 cases were included in the analysis of reoperation rates for septic and aseptic revision TKAs. Pooled data from these studies showed a higher reoperation rate for septic revision TKAs than for aseptic revision TKAs (RR, 1.98; 95% CI, 1.50 to 2.62; p < 0.00001) (Fig.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Two nurses and one private doctor (see Acknowledgements) found and visited non-responders. 9,10 Clinical evaluations were performed using the Knee Society rating system. 8 Results were classified as excellent (80 to 100 points), good (70 to 79 points), fair (60 to 69 points), or poor (< 60 points).…”
Section: Methodsmentioning
confidence: 99%
“…In the remaining 10 studies, 2-stage revision TKA was performed for septic failure [19][20][21][22][23][24][25][26][27][28] . In the analysis pooling these studies (395 septic revision TKA cases and 975 aseptic revision TKA cases), the infection rate was also significantly higher in the septic revision TKA group (OR, 4.14; 95% CI, 2.33 to 7.36; p < 0.00001; I 2 = 22%) (Fig.…”
Section: Infection Rates After Revision Tkamentioning
confidence: 99%
“…Finally, when 287 cases of septic revision TKA and 339 cases of revision TKA for aseptic loosening were compared 9,18,[25][26][27] , the infection rate was again higher in the septic revision TKA group (OR, 4.45; 95% CI, 2.28 to 8.70; p < 0.0001; I 2 = 0%) (Fig. 4).…”
Section: Infection Rates After Revision Tkamentioning
confidence: 99%